Ability to Understand German Language Spoken Text Through Musik Media at the German Language Education Studi Program FKIP Unpatti Ambon - Serpara, Henderika; Karuna, Kalvin; Nikijuluw, Maria (KnE Social Sciences, 2024)
Oral-text comprehension is one of the essential conditions that ensure interactive oral communication. Oral texts are not only understood as utterances delivered during oral communication but also in the form of announcements, notifications, discussions through audio media. In German language learning, Hörverstehen material is more focused on oral texts delivered through the media. This study aims to describe whether there is a difference in oral-text comprehension ability before and after using music media in learning. This research is an experiment involving 11 students who attended the B1 Preparation Course at the Pattimura University Language Study Center as participants. The activity began with a pretest and then continued with a treatment using music as a medium and then ended with a post-test. The results analysis show that the application of music as a medium in language learning, especially in understanding spoken text in German, contributes positively to the competence of understanding spoken text. The positive contribution is possible because the application of music in learning can condition two things at once, namely creating joyful learning and habituation of word sounds in song verses in students' hearing. The conclusion is based on the results of statistical calculations which show that the calculation value of t = (5.17) is greater than Ttab (1.81) at a significant level of 0.05. On the basis of this finding, it is hoped that this finding can be used as an alternative in improving the ability to understand German spoken text. Keywords: Oral text comprehension skills, music media, language learning, listening skills